2017
DOI: 10.3389/fnagi.2017.00122
|View full text |Cite
|
Sign up to set email alerts
|

Feature Binding of Common Everyday Items Is Not Affected by Age

Abstract: There is a surge of studies confirming that old age spares the ability to bind in visual working memory (VWM) multiple features within singular object representations. Furthermore, it has been suggested that such ability may also be independent of the cultural background of the assessed individual. However, this evidence has been gathered with tasks that use arbitrary bindings of unfamiliar features. Whether age spares memory binding functions when the memoranda are features of everyday life objects remains le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
1
23
0
1
Order By: Relevance
“…The task has been described in details elsewhere (Hoefeijzers et al., 2017). Briefly, the procedure was very similar to the binding tasks described above.…”
Section: Resultsmentioning
confidence: 99%
“…The task has been described in details elsewhere (Hoefeijzers et al., 2017). Briefly, the procedure was very similar to the binding tasks described above.…”
Section: Resultsmentioning
confidence: 99%
“…For conjunctions of different surface features (such as colour and shape), a host of studies has found little indication of a specific decrement of binding memory with age, even though overall memory performance is generally worse in older than younger adults (Brockmole, Parra, Della Sala, & Logie, ; Parra, Abrahams, Logie, & Della Sala, ; Isella, Molteni, Mapelli, & Ferrarese, ; Read, Rogers, & Wilson, ; Hoefeijzers, González Hernández, Magnolia Rios, & Parra, ; with conflicting results only in a single experiment in Brown & Brockmole, ). In contrast, some earlier studies did report a specific decrement in performance for tasks requiring binding of features or objects to location (Brockmole & Logie, ; Cowan et al ., ; Mitchell, Johnson, Raye, & D'Esposito, ; Mitchell, Johnson, Raye, Mather, & D'Esposito, ).…”
Section: Binding In Ageing and Clinical Conditionsmentioning
confidence: 99%
“…By providing information as to what went where, context could potentially confer an even greater benefit in older than younger adults, if it reduces binding errors that are otherwise more common in older adults. As a caveat, however, binding errors are not found in all circumstances and may depend on task details (Brockmole et al, 2008;Parra et al, 2009;Allen et al, 2013;Pertzov et al, 2015;Hoefeijzers et al, 2017). Furthermore, it might be that older adults do (or could) more strongly exploit the strategy of elaborating on the relationships between items.…”
Section: Introductionmentioning
confidence: 99%
“…colour/orientation/location) and encoding durations (e.g. 200 -2000 ms), although the age-related binding errors may be specific to reporting what went where, rather than bindings between non-spatial features (Brockmole et al, 2008;Parra et al, 2009;Hoefeijzers et al, 2017).…”
Section: Introductionmentioning
confidence: 99%